Embolotherapy for Neuroendocrine Tumors - Nadolski, Gregory J.; Soulen, Michael C. (Digestive Disease Interventions, 2019)
The most frequent solid organ involved in metastatic neuroendocrine tumors (NET) is the liver. Hepatic metastases occur during the lifetime of 46% to 93% of patients with NETs. Intra-arterial embolotherapies are palliative and should be used for patients with unresectable disease not amenable to resection or ablation. The most widely accepted indications for liver embololization for NET metastases are progression of unresectable hepatic metastases threatening liver function and palliation of hormone-related symptoms uncontrolled by somatostatin analogues. This article will discuss patient selection and administration of all embolotherapies currently used for palliation of neuroendocrine liver metastases.
Keywords: Neuroendocrine Tumors; hepatic metastases; embolotherapy